2001
DOI: 10.1142/s0218271801001542
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence-Induced Violations of Einstein Equivalence Principle

Abstract: In this essay it will be shown that Decoherence Model and Einstein Equivalence Principle are conceptually incompatible. In other words, assuming only the validity of the Weak Equivalence Principle the present work concludes that we face two possibilities: (i) if Decoherence Model provides a correct description of nature at quantum level, then there are systems which violate Local Position Invariance, or, (ii) if all the postulates behind Einstein Equivalence Principle are valid, even on quantum realm, then Dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Examples are the study reported in Ref. [168], which obtained violations of the Equivalence Principle from quantum-spacetime-induced decoherence, the study based on noncritical Liouville String Theory reported in Ref. [169], and the study based on metric flluctuations reported in Ref.…”
Section: Planck-scale Departures From the Equivalence Principlementioning
confidence: 99%
“…Examples are the study reported in Ref. [168], which obtained violations of the Equivalence Principle from quantum-spacetime-induced decoherence, the study based on noncritical Liouville String Theory reported in Ref. [169], and the study based on metric flluctuations reported in Ref.…”
Section: Planck-scale Departures From the Equivalence Principlementioning
confidence: 99%